The evaluation of Bacillus thuringiensis subspecies israelensis based biopesticides for the control of southern African malaria vectors - Ketseoglou, Irene (My University, 2012)
Malaria, one of the most deadly vector-borne diseases in the world, is transmitted by the bite of an infected female Anopheles mosquito. Since there are several problems arising from current control programs, alternative control strategies for malaria-carrying vectors are required. The objective of this thesis was to evaluate a recombinant Anabaena sp. strain PCC 7120, Anabaena PCC 7120#11 (PCC 7120#11), as an agent to control southern African malaria vectors. Select Bacillus thuringiensis subspecies israelensis (Bti) toxin genes, cry4Aa and cry11Aa, had previously been cloned into Anabaena sp. strain PCC 7120. Evaluation of the potential of PCC 7120#11 and Bti as control agents of southern African malaria vectors required the evaluation of the larvicidal activity of PCC 7120#11 and Bti against several important malaria vectors. This study showed that all five of the African anopheline species evaluated in laboratory bioassays (Anopheles gambiae, Anopheles arabiensis, Anopheles funestus, Anopheles quadriannulatus, and Anopheles merus) were susceptible to Bti, whereas PCC 7120#11 exhibited high larvicidal activity against four of the five anopheline species. The low larvicidal activity of PCC 7120#11 against An. funestus could be due to the absence of the other Bti toxins in PCC 7120#11 or differences in the structure and/or density of specific midgut toxin receptors for the Cry4Aa or Cry11Aa proteins. The Standardized Aquatic Microcosm (SAM), a synthetic multi-species system consisting of a chemically defined medium with the same species and concentration of photosynthetic microorganisms (PMOs) and invertebrates, was used to comprehensively evaluate the effects of Bti and PCC 7120#11 in an aquatic environment. The SAM experiments showed that Bti was non-toxic to the invertebrates evaluated and did not significantly affect any of the other variables evaluated in the microcosms. Bti was shown to be an environmentally friendly control agent.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy, Johannesburg, 2012
Keywords: Bacillus thuringiensis; Mosquitoes--Control